Cytokines and chronic liver disease - Fainboim, Leonardo (2007)
From an immunological point of view, the healthy liver has been usually associated with the phenomenon of tolerance. A microenvironment of regulatory cytokines produced by liver Kuppfer cells and liver sinusoidal endothelial cells has contributed, together with resident dendritic cells, to generate a tolerogenic environment in this tissue. In this review we discussed the intrahepatic responses to different sorts of liver injury, such as hepatotrophic viruses, alcohol or putative self-antigens. In each case we analyzed the impact of different cytokines in the clinical outcome of the different pathological situations.